Out of the Shadows: Using Human Rights Approaches to Secure Dignity and Well-Being for People with Mental Disabilities - Yamin, Alicia Ely (Public Library of Science, 2005)
A human-rights-based policy on mental health is urgently needed, argue Yamin and Rosenthal. Around half a billion people suffer from a mental or behavioral disorder, yet only a small minority receive even the most basic treatment